BOROBUDUR SEBAGAI MEDIA PEMBELAJARAN DARI ELEMEN SEJARAH DALAM KURIKULUM MERDEKA MATA PELAJARAN AGAMA BUDDHA DAN BUDI PEKERTI - Girivirya, Sulaiman (Jurnal Kelola: Jurnal Ilmu Sosial, 2023)
The Ministry of Education and Culture (Kemendikbudristek) is aware of a threatening learning crisis caused by the Covid-19 pandemic. The Ministry of Education and Culture implements the Independent Curriculum in the hope of increasing students' understanding of basic literacy. As a subject, Buddhism and Moral Education in schools also underwent changes. Using a systematic literature review method, this article offers a study of Borobudur as a learning medium on historical elements found in the independent curriculum in the subject of Religion and Behavior.